Boats - Morse, Jenifer Corr. (Woodbridge, CT : Blackbirch Press, 2001)
Provides photographs and descriptions of ten of the fastest boats ever made, including the Trieste, the SeaCat Ferry, and the VSV Wave Piercer.
Includes bibliographical references (p. [24]) and index.
5.9.
5.9
3-6
Keywords: Boats and boating -- Juvenile literature; Jet boats -- Juvenile literature; Ships -- Juvenile literature; Boats and boating; Jet boats; Motorboats; Submarines; Boats and boating; Jet boats; Motorboats; Ships; Submarines